Macrophages and neutrophils express IFNλs in granulomas from Mycobacterium tuberculosis-infected nonhuman primates - Talukdar, Priyanka; Junecko, Beth F.; Lane, Daniel S.; Maiello, Pauline; Mattila, Joshua T. (Frontiers in Immunology, 2022)
Granulomas are the hallmark of Mycobacterium tuberculosis (Mtb) infection. Cytokine-mediated signaling can modulate immune function; thus, understanding the cytokine milieu in granulomas is critical for understanding immunity in tuberculosis (TB). Interferons (IFNs) are important immune mediators in TB, and while type 1 and 2 IFNs have been extensively studied, less is known about type 3 IFNs (IFNλs) in TB. To determine if IFNλs are expressed in granulomas, which cells express them, and how granuloma microenvironments influence IFNλ expression, we investigated IFNλ1 and IFNλ4 expression in macaque lung granulomas. We identified IFNλ expression in granulomas, and IFNλ levels negatively correlated with bacteria load. Macrophages and neutrophils expressed IFNλ1 and IFNλ4, with neutrophils expressing higher levels of each protein. IFNλ expression varied in different granuloma microenvironments, with lymphocyte cuff macrophages expressing more IFNλ1 than epithelioid macrophages. IFNλ1 and IFNλ4 differed in their subcellular localization, with IFNλ4 predominantly localizing inside macrophage nuclei. IFNλR1 was also expressed in granulomas, with intranuclear localization in some cells. Further investigation demonstrated that IFNλ signaling is driven in part by TLR2 ligation and was accompanied by nuclear translocation of IFNλR1. Our data indicate that IFNλs are part of the granuloma cytokine milieu that may influence myeloid cell function and immunity in TB.